ANALISIS ADOPSI LAYANAN INTERNET BANKING OLEH NASABAH PERBANKAN DI PEKANBARU (Technology Acceptance Model) Eni Noviarni - Eni Noviarni (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2014)
This study aims to analyze the factors that affect adoption of internet banking services by bank customers in the city of Pekanbaru to approach the Technology Acceptance Model (TAM). The research method is a survey with descriptive analysis approach. Data processed and analyzed with statistical models using mul tiple regression help of a computer using SPSS software version 17.Conclusion of this study indicate that the magnitude of usefulness, ease of use, awareness, risk and social influences affect the adoption of Internet banking by bank customers in Pekanbaru.